2023
DOI: 10.3390/agriculture13061226
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of the Herbicide Aclonifen and Its Soil Metabolites on Soil and Aquatic Environments

Abstract: Aclonifen is an herbicide with a global market that is expected to grow in the period 2021–2027. This study focuses on revealing the effects of both aclonifen and of its soil metabolites on aqueous and soil environments. The soil’s physicochemical parameters and activities of enzymes found in the soil (urease, dehydrogenase, catalase, alkaline phosphatase) were evaluated in laboratory conditions for soil treated with various doses of aclonifen (from half of a normal dose, 2.1 g/ha, to three times the normal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…This was is agreement with the experimental results, which showed that myclobutanil produced no changes in UA. A similar result was observed for the triticonazole enantiomers [9] and for aclonifen and its metabolites [49] that could not bind to the active site of this enzyme. This was explained by the obtuseness, rigidity and hydrophilicity of the catalytic site of urease [60].…”
Section: Computational Approachsupporting
confidence: 83%
See 1 more Smart Citation
“…This was is agreement with the experimental results, which showed that myclobutanil produced no changes in UA. A similar result was observed for the triticonazole enantiomers [9] and for aclonifen and its metabolites [49] that could not bind to the active site of this enzyme. This was explained by the obtuseness, rigidity and hydrophilicity of the catalytic site of urease [60].…”
Section: Computational Approachsupporting
confidence: 83%
“…PA was estimated on the basis of the reaction of ninhydrin with the amino acids that resulted from the hydrolysis of the gelatin used as a substrate, which was the method proposed by Drăgan-Bularda [48]. These methods have previously been applied in order to evaluate the effects on the activity of these enzymes of the herbicides aclonifen [49], S-metolachlor [50] and oxyfluorfen [51], and on the triazole fungicides triticonazole [9] and difenoconazole [52]. The soil treated with myclobutanil at different doses and the control soil were incubated for a period of 28 days under laboratory conditions, and the activity of each enzyme was determined every 7 days.…”
Section: Enzymatic Activity Analysesmentioning
confidence: 99%
“…The mechanisms involved in the transformation of herbicides depend on several factors such as their physicochemical properties, soil characteristics, and climatological conditions, and in many cases, they are not completely known [3]. Therefore, monitoring the presence of herbicides in soil is considered crucial, not only to ensure environmental quality, but also to gain knowledge about their persistence, dissipation mechanisms, and final fate [4,5].…”
Section: Introductionmentioning
confidence: 99%